2007
DOI: 10.1186/ar2272
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with the loss of cartilage volume on weight-bearing areas in knee osteoarthritis patients assessed by quantitative magnetic resonance imaging: a longitudinal study

Abstract: The objective of this study was to identify, on a symptomatic knee osteoarthritis (OA) cohort, the risk factors associated with the progression of the disease. More specifically, we investigated the correlation between knee cartilage volume loss from subregions over the span of 24 months by means of quantitative magnetic resonance imaging (qMRI) with demographic, clinical, radiological, and MRI structural changes.A cohort of 107 patients with knee OA selected from a large trial evaluating the effect of a bisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
221
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(252 citation statements)
references
References 22 publications
22
221
3
6
Order By: Relevance
“…Indeed, magnetic resonance imaging (MRI) revealed the presence of bone marrow lesions (hypersignal), which increased in size gradually over time [10][11][12]. Using this technology, the presence of oedema-like lesions in subchondral bone marrow and bone attrition were found to be strong indicators of bone turnover indices as well as structural deterioration in knee OA.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, magnetic resonance imaging (MRI) revealed the presence of bone marrow lesions (hypersignal), which increased in size gradually over time [10][11][12]. Using this technology, the presence of oedema-like lesions in subchondral bone marrow and bone attrition were found to be strong indicators of bone turnover indices as well as structural deterioration in knee OA.…”
Section: Osteoarthritismentioning
confidence: 99%
“…However, imaging methods other than radiography were recently used to detect markers or risk factors for this disease. The literature reveals that MRI is very useful for the assessment of disease activity and the determination not only of disease progression but also of early events [10,11]. In this context, meniscal lesions and bone marrow oedema were demonstrated to be important risk factors for OA progression [12,108].…”
Section: Bone Markers In Oamentioning
confidence: 99%
“…Metrics of cartilage morphology (volume, thickness, and others) based on MRI have been shown to be reproducible in single (1,3) and multicenter studies (4) and hold promise for evaluating the treatment response of structure/disease-modifying drugs. Several studies have reported the rate and sensitivity to change of cartilage morphology measures in participants with OA (5)(6)(7)(8)(9)(10)(11) and healthy persons (12-15) using 1.5T (1,3,16) or 3T MRI (17)(18)(19). Some of these studies have compared measures of change based on MRI to joint-space narrowing from radiographs (7,10,11,17,20).…”
mentioning
confidence: 99%
“…For instance, it is known that the presence of meniscal lesions or BML is predictive of disease progression (5,11,26,(31)(32)(33)(34). We are now proposing the VM %Fat as a novel and independent risk factor for knee OA progression.…”
Section: Discussionmentioning
confidence: 99%